The habitable zone of inhabited planets (2014)
ABSTRACT: In this paper we discuss and illustrate the hypothesis that life substantially alters the state of a planetary environment and therefore, modifies the limits of the HZ as estimated for an uninhabited planet. This hypothesis lead to the introduction of the Habitable Zone for Inhabited planets (hereafter InHZ), defined here as the region where the complex interaction between life and its abiotic environment is able to produce plausible equilibrium states with the necessary physical conditions for the existence and persistence of life itself. We support our hypothesis of an InHZ with three theoretical arguments, multiple evidences coming from observations of the Earth system, several conceptual experiments and illustrative numerical simulations. Conceptually the diference between the InHZ and the Abiotic HZ (AHZ) depends on unique and robust properties of life as an emergent physical phenomenon and not necesarily on the particular life forms bearing in the planet. Our aim here is to provide conceptual basis for the development of InHZ models incorporating consistently life-environment interactions. Although previous authors have explored the effects of life on habitability there is a gap in research developing the reasons why life should be systematically included at determining the HZ limits. We do not provide here definitive limits to the InHZ but we show through simple numerical models (as a parable of an inhabited planet) how the limits of the AHZ could be modified by including plausible interactions between biota and its environment. These examples aim also at posing the question that if limits of the HZ could be modified by the presence of life in those simple dynamical systems how will those limits change if life is included in established models of the AHZ.